2015
DOI: 10.1016/j.fuproc.2015.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Low temperature ignition of biomass

Abstract: Biomass is an especially reactive fuel. There have been large increases in the transportation and utilization of biomass fuels over the past 10 years and this has raised concerns over its safe handling and utilization. Fires, and sometimes explosions, are a risk during all stages of fuel production as well as during the handling and utilization of the product. This paper presents a method for assessing ignition risk and provides a ranking of relative risk of ignition of biomass fuels. Tests involved singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(59 citation statements)
references
References 13 publications
1
56
0
Order By: Relevance
“…The minimum ignition temperature of biomass dust layers and their blends are given in Table 5 together with the corresponding ignition delay times. There is an inverse relationship between minimum ignition temperature and ignition delay as seen by Jones et al 8 in their study where low temperature ignition of biomass was the focus. Consistent with the TMWL values obtained from the TGA/DTG measurements, pine is less reactive than miscanthus and there is a difference of 40 o C in the minimum ignition temperatures.…”
Section: Determination Of Ignition Characteristics Of Solid Biomass Dmentioning
confidence: 86%
See 1 more Smart Citation
“…The minimum ignition temperature of biomass dust layers and their blends are given in Table 5 together with the corresponding ignition delay times. There is an inverse relationship between minimum ignition temperature and ignition delay as seen by Jones et al 8 in their study where low temperature ignition of biomass was the focus. Consistent with the TMWL values obtained from the TGA/DTG measurements, pine is less reactive than miscanthus and there is a difference of 40 o C in the minimum ignition temperatures.…”
Section: Determination Of Ignition Characteristics Of Solid Biomass Dmentioning
confidence: 86%
“…Hence, the single oxidation temperature used by Ramirez et al (Tcharac) was replaced in this study by the temperature of the maximum rate of weight loss temperature (TMWL) in air stream. As discussed in the study on low temperature ignition of biomass by Jones et al 8 , a single peak, Tcharac, was not observed in TGA studies under oxygen. The apparent first order activation energy, Ea, was calculated from the TGA weight loss curve and this parameter was also used in the risk ranking method.…”
Section: Solid Fuel Characterization -Proximate Analysis Reaction Ramentioning
confidence: 87%
“…The results of the experimental studies of the ignition of the wood particles of two groups have been given: large d up to 3 mm, and small~210 mm in Ref. [22]. The large particles have been cubes (3 Â 3x3 mm) based on an olive tree or pine, or Miscanthus needles (3 Â 3 mm).…”
Section: A Brief Review Of the Experimental Studies Of The Wood Partimentioning
confidence: 99%
“…As a result, the ignition delay times have been determined. The ambient temperature (Tg) has been varied [22] in the range from 490 to 670 K. In this case, the main task of the study [22] has been to determine the minimum Tg value sufficient for igniting wood. The effect of the particle form on the ignition characteristics has not been studied.…”
Section: A Brief Review Of the Experimental Studies Of The Wood Partimentioning
confidence: 99%
“…Then, the TG curve tangent at point B intersects with the horizontal line of weight loss beginning at point C. The corresponding temperature at point C is defined as the ignition temperature (point D). Figure 5 demonstrates the method (Jones et al 2015). …”
Section: Computational Analysis Of Comprehensive Combusting Charactermentioning
confidence: 99%